ANALISIS FAKTOR YANG MEMPENGARUHI TRANSFER PRICING ANTAR PERUSAHAAN KONSOLIDASI DI INDONESIA - Amalia Nessa Arlinda; Ayuk Yuliana; Endang Kartini Panggiarti (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The development of national companies into international ones raises the potential for transfer pricing which can reduce state tax revenues. This study aims to describe aspects of transfer pricing from an accounting and tax perspective, the factors that most influence the consolidated company's decision to practice transfer pricing, and how to minimize the risk of loss of state revenue as a result of transfer pricing practices. Qualitative research with the type of descriptive statistical research and secondary data types obtained from various collections of articles through the Google Scholar page using the keyword "transfer pricing in Indonesia." The method used is data reduction and the research results include: (1) methods for calculating reasonable transfer prices in transfer pricing, namely CUP, RPM, Cost Plus Method, PSM, and TNMM. (2) The Director General of Taxes has the authority to redefine the amount of income and tax deductions and debts for taxpayers who have a special relationship with other taxpayers based on article 18 paragraph 3 of the Income Tax Law (3) Factors affecting transfer pricing, including tax avoidance, bonus mechanisms, and dept. covenant. (4) risk mitigation in minimizing the risk of loss of state revenue due to transfer pricing.